THE TWO SIDES OF LEADERSHIP: WHEN GENDER AND CEO EXPERIENCE SHAPE THE CAPITAL STRUCTURE OF THE ENERGY SECTOR - Luky Patricia Widianingsih; Catharine Felicia (Research In Management and Accounting (RIMA), 2026)
Capital structure decisions are an essential aspect of corporate financial strategy, particularly in the energy sector, which is characterized by high risk and substantial investment needs. In this context, internal factors such as CEO characteristics, profitability, and liquidity play important roles in financing decisions. This study focuses on the influence of CEO gender, CEO tenure, profitability (Return on Assets / ROA), and liquidity (Current Ratio) on leverage (Debt-to-Equity Ratio / DER) in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2023 period. The results show that CEO gender has a significant positive effect on leverage (DER), while CEO tenure and liquidity have significant negative effects on leverage (DER). Profitability, however, does not have a significant impact. These findings emphasize that in energy sector companies listed on the IDX, considerations of leadership characteristics and the company's internal financial condition are key determinants in capital structure decisions.